Vaguely sympathetic dysfunction in the digestive tract - Monge, Carlos (1927)
We assert now that our work will not be checking the doctrine of Eppinger and Hess vagotonia and simpaticonía, however - as Professor Walter Alvarez, the famous physiologist at the University of California says - the magic attraction that these expressions have in the minds of clinicians who have found them easy key that explains all kinds of syndromes.